2012
DOI: 10.1002/jor.22280
|View full text |Cite
|
Sign up to set email alerts
|

Toward an understanding of the short bone phenotype associated with multiple osteochondromas

Abstract: Purpose Individuals with multiple osteochondromas (MO) demonstrate shortened long bones. Ext1 or Ext2 haploinsufficiency cannot recapitulate the phenotype in mice. Loss of heterozygosity for Ext1 may induce shortening by steal of longitudinal growth into osteochondromas or by a general derangement of physeal signaling. Methods We induced osteochondromagenesis at different time points during skeletal growth in a mouse genetic model, then analyzed femora and tibiae at 12 weeks using micro-CT and a point-distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…However, recent experiments show no change in overall bone volume and no correlation between forearm shortening and the presence of an osteochondroma. This work indicates that HS loss may be important for directing the ratio between peripheral and longitudinal growth (Jones et al, ). Exostoses can also sometimes occur in craniofacial elements such as the mandible (Ruiz and Lara, ).…”
Section: Introductionmentioning
confidence: 85%
“…However, recent experiments show no change in overall bone volume and no correlation between forearm shortening and the presence of an osteochondroma. This work indicates that HS loss may be important for directing the ratio between peripheral and longitudinal growth (Jones et al, ). Exostoses can also sometimes occur in craniofacial elements such as the mandible (Ruiz and Lara, ).…”
Section: Introductionmentioning
confidence: 85%
“…This gave rise to frequent osteochondromas on the appendicular skeleton, indicating that LOH is the inductive event for osteochondroma [17]. In addition, low-prevalence LOH for Ext1 in physeal chondrocytes was enough to mimic a short-bone phenotype, indicating that LOH drives the short-bone phenotypes associated with MHE [16]. Furthermore, the model indicated that the physeal chondrocyte is the cell of osteochondroma origin, rather than the ossification groove of Ranvier as was previously speculated [17].…”
Section: Mouse Models For Pathogenesismentioning
confidence: 66%
“…More and bigger osteochondromas means more severe MO and thus more influence of the gene dysfunction on the biochemical setup. A mouse study by Jones also does not support the relationship between the volume of osteochondromas and the growth plate influence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the systemic influence of the gene defect and its relationship with the growth plate as a possible cause of the short or diminished stature. Jones et al [ 32 ] demonstrated in a mouse genetic model that mice with osteochondromas had shorter femora and tibiae than controls. The volume of the osteochondromas, however, did not correlate with longitudinal shortening.…”
Section: Introductionmentioning
confidence: 99%